PENGARUH PENAMBAHAN DAUN LAMTORO TERHADAP KUALITAS KOMPOS KERTAS-LAMTORO DAN PEMANFAATANNYA TERHADAP PERTUMBUHAN TANAMAN BAYAM MERAH - ZULIYANTI NINGSIH, RINA Zuliyanti (Universitas Negeri Surabaya, 2013)
One alternative to use the sludge paper mill in order not to cause pollution in the environment is to use it as compost. Paper-lamtoro compost is expected to increase the levels of nutrients content, especially nitrogen (N) level. The purpose of this study were (1) to describe the quality of paper-lamtoro compost in the levels of N, P, K and C/N ratio and (2) to describe the effect of the concentrations of paper-lamtoro compost on the growth of red spinach plants. The study consisted of two phases, the first was the composting process and the second was the utilization of paper-lamtoro compost on plant growth red spinach plants performed experimentally using Randomized Block Design with one factor treatment, the concentration of compost includes 4.30 g, 6.45 g, 8.60 g, 10.45 g and 0.20 g of urea as a control. These treatment were repeated five times to obtain 25 samples. The parameters were the levels of N, P, K and C/ N ratio and the growth of the red spinach plants which includes the number of leaves, plant height and wet plant biomass. The first stage of data analysis was performed by comparing the descriptive criteria for nutrient content of the soil by Hardjowigeno (2003), and the second stage using analysis of variance (ANOVA), followed by LSD test to determine differences between treatments. The results showed that (1) the addition of Leucaena glauca leaves affect the quality of nutrient content of N, P, K and C/ N ratio of paper-lamtoro compost produced. The level of N, P, K and C/ N ratio were 2.14%; 0.35%, 0.71% and 12.80% respectively (2) the concentration of paper-lamtoro compost affect significantly on the growth of red spinach plant. The best growth was found in the concentration of 10.75 g compost/ 3000 g planting medium.